If You Don’t Know Me by Now: The Failure of Care in “Bartleby, The Scrivener” - Kari Nixon (Disability Studies Quarterly, 2014)
"Bartleby, the Scrivener" is one of the most haunting tales of the nineteenth century. Criticism has centered on analysis of both the narrator and Bartleby himself, taking up the question of whether or not the narrator ultimately fulfills his moral obligations to Bartleby. I believe an approach to the story, however, which takes as its starting point a critique of the medical model of disability helps elucidate this issue. This approach makes it clear that given his situation in a world which values a medically inspired model of understanding difference, the narrator, benevolent as he may be, can never do enough for Bartleby, because, given this situation, he can never ask the right questions of Bartleby or posit appropriate solutions for him. I conclude my argument with a consideration of critical complicity in this issue as critics attempt to classify Bartleby, thereby following in the narrator's misguided footsteps.
Keywords: 19th-century literature; medical models; Bartleby; Melville; diagnosis